Odpowiedź :
Odpowiedź:
1.
(3x²y - 2x)(-2y + 3xy) - (5xy + 8y)(-x + 3) = -6x²y² - 9x³y + 4xy - 6x²y -
- (-4x²y + 15xy - 8xy + 24y) = -6x²y² - 9x³y + 4xy - 6x²y + 4x²y - 7xy - 24y =
= -6x²y² - 9x³y - 3xy -2x²y - 24y
2.
-7a(ab + 2a²b³) + (3a - 5b)(4b - 8a) = -7a²b - 14a³b³ + 12ab - 24a² - 20b² + 40ab
= -7a²b - 14a³b³ + 52ab - 24a² - 20b²
3.
5x²y(-2x + 4y) - (x³y - 7x²y²) + 7,5x²y² - 0,75xy = -10x³y + 20x²y² - x³y + 7x²y² +
+ 7,5x²y² - 0,75xy = -11x³y + 34,5x²y²
4.
(2√2x - √3y)(2√2x + √3y) - (2√2x - √3y)(2√2x - √3y) =
= 4 * 2x² - 3y² - (2√2x - √3y)² = 8x² - 3y² - 4 * 2x² + 4√6xy - 3y² =
= -6y² + √6xy
5.
(1 2/3a + 2 1/2b)(1 2/3a + 1 1/2b) - 2 2/5(a² + 3ab - 5b²) =
= (1 2/3a + 2 1/2b)² - 12/5(a² + 3ab - 5b²) = (5/3a + 5/2b)² - 12/5a² + 36/5ab -
- 12b² = 25/9a² + 2 * 25/6ab + 25/4b² = 2 7/9a² + 25/3ab + 6 1/4b²
6.
(7,5x - 3,4xy)(-2x + 5y) - 2,8(5x² - 10xy) = -15x² + 37,5xy + 6,8x²y - 17xy² -
- 14x² + 28xy = -29x² + 6,8x²y - 17xy² + 28xy
7.
(√6ab - √2a)(2√2a + √6ab) - 2√3a(3ab - 2√12a) =
= 2√12a²b + 6a²b² - 2*2a² - √12a²b - 6√3a²b + 4√36a² =
= √12a²b + 6a²b² - 4a² - 6√3a²b + 4*6a² = 20a² + √12a²b + 6a²b² - 6√3a²b = 20a² - 6√3a²b + √4a²b * √3a²b = 20a² - 6√3a²b + 2√3a²b =
= 20a² - 4√3a²b
Szczegółowe wyjaśnienie: